2018
DOI: 10.1186/s12918-018-0577-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new progestogen-associated networks in mammalian ovulation using bioinformatics

Abstract: BackgroundProgesterone plays an essential role in mammalian ovulation. Although much is known about this process, the gene networks involved in ovulation have yet to be established. When analyze the mechanisms of ovulation, we often need to determine key genes or pathways to investigate the reproduction features. However, traditional experimental methods have a number of limitations.ResultsData, in this study, were acquired from GSE41836 and GSE54584 which provided different samples. They were analyzed with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In another study ovarian proteome of hyper-prolificacy sheep was analyzed and more than 100 identified proteins were classified in carbohydrate transport and metabolism [ 76 ]. Also, Yang et al [ 77 ] using transcriptome analysis, reported galactose metabolism and fructose and mannose metabolism as biological pathways affecting ovulation. Many GO terms related to cell communication such as biological adhesion (GO:0022610), cell adhesion (GO:0007155), cell junction (GO:0030054), and cell-cell adherens junction (GO:0005913) were identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study ovarian proteome of hyper-prolificacy sheep was analyzed and more than 100 identified proteins were classified in carbohydrate transport and metabolism [ 76 ]. Also, Yang et al [ 77 ] using transcriptome analysis, reported galactose metabolism and fructose and mannose metabolism as biological pathways affecting ovulation. Many GO terms related to cell communication such as biological adhesion (GO:0022610), cell adhesion (GO:0007155), cell junction (GO:0030054), and cell-cell adherens junction (GO:0005913) were identified.…”
Section: Discussionmentioning
confidence: 99%
“…cGMP) to support the oocyte development, metabolism, and hemostasis [ 79 ]. Many genomics, transcriptomics, and proteomics studies reported many pathways related to both cell adhesion and gap junction process as pathways which has vital roles in prolificacy [ 49 , 62 , 77 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that FAF1 , Fas-associated protein factor 1, is expressed in the cytoplasm of growing oocyte of the ovary [ 63 ]. Yang et al have provided that LRP8 is the progestogenic-associated gene [ 64 ]. These results suggest that the tissue-specific circRNAs might regulate the transcriptions of their parental genes to involve in the onset of puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Although PDEs and cyclic nucleotides play a critical role in the ovary, namely in regulating folliculogenesis, oocyte maturation, and ovulation, PDE10A has not been widely studied in this regard [28,29]. The most notable research on PDE10A and ovulation comes from a bioinformatics analysis of microarrays in hCG stimulated mouse preovulatory follicles, where PDE10A was reported to be one of four essential genes in progesterone-related ovulatory networks [30].…”
Section: Introductionmentioning
confidence: 99%